DESIGN AND EVALUATION OF EXTENDED RELEASE RANOLAZINE LIQUISOLOID TABLETS USING PLACKETT BURMAN SCREENING DESIGN - Kuchekar, Shantanu B; Mohite, Shrinivas K (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: The short biological half-life of Ranolazine (RAN) and consequently the difficulties in maintaining the desired concentrations in the blood, determined the need for the development of an extended release formulation which can achieved by developing a matrix tablet using Eudragit L100-55. Furthermore, including some materials like polyvinylpyrrolidone to liquid medication (microsystems), it would be possible to produce dry powder formulations containing liquid with high concentration of the drug. The aim of the present study was to develop RAN liquisolid tablets using Plackettâ€“Burman (PB) design to screen the effect of five formulation and process factors on the formulation. Methods: RAN liquisolid tablets were prepared by liquisolid technique using PB design to screen the effect of five formulation and process factors. The RAN liquisolid formulations were characterized by pre and post compression parameters, differential scanning calorimetry, powder X-ray diffraction, scanning electron microscopy, and in-vitro drug release. Results: Parameters such as Neusilin US2, Aerosil 200, polyethylene glycol grades (PEG) 400, polyvinyl pyrrolidone (PVP) K30, and Eudragit L100- 55 showed an influential effect on the selected responses angle of repose, thickness, and hardness as observed in Pareto charts of PB design. Hence, liquisolid technique was selected to develop the extended release liquisolid tablets of RAN. Conclusion: PB design was proved to be appropriate tool to study effect of Neusilin US2, Aerosil 200, PEG 400, PVP K30, and Eudragit L100-55 on the response variables and to recognize the most influencing factor by using liquisolid technique. Keywords: Ranolazine, Liquisolid technique, Eudragit L100 55, Plackettâ€“Burman. Â